Preliminary Findings on the Potential Use of Magnetic Resonance Elastography to Diagnose Lacunar Infarction - Wang L; Ke J; Hu X; Zhu M; Yu Y (Neuropsychiatric Disease and Treatment, 2022)
Lingjie Wang,* Jun Ke,* Xiaoyin Hu, Mo Zhu, Yixing Yu Department of Radiology, The First Affiliated Hospital of Soochow University, Soochow, People’s Republic of China*These authors contributed equally to this workCorrespondence: Mo Zhu; Yixing Yu, Department of Radiology, The First Affiliated Hospital of Soochow University, No. 188 Shizi Road, Soochow, 215000, People’s Republic of China, Tel +86-512-67973009, Fax +86-512-67973061, Email zhumo001@126.com; yuyixing@163.comPurpose: Lacunar infarction is usually diagnosed by conventional technologies, such as CT and diffusion weighted imaging (DWI). To improve the accuracy of diagnosis, neurocognitive screening is still needed. Therefore, additional imaging methods that can assist and provide more accurate and rapid diagnostics are urgently needed. As an initial step towards potentially using MR elastography (MRE) for such diagnostic purposes, we tested the hypothesis that the mechanical properties of tissue in the vicinity of cerebral vasculature change following lacunar infarction in a way that can be quantified using MRE.Patients and Methods: MRE and MR angiography (MRA) images from 51 patients diagnosed with lacunar infarction and 54 healthy volunteers were acquired on a 3T scanner. All diagnoses were confirmed by matching neurocognitive test results to locations of flow obstruction in MRA. ROIs of the cerebral vessels segmented on the MRA images were mapped to the MRE images. Interpolation-based inversion was applied to estimate the regional biomechanical properties of ROIs that included cerebral vessels. The effects of lacunar infarction, sex, and age were analyzed using analysis of covariance (ANOCOVA).Results: Shear moduli over vessel ROIs were significantly lower for the lacunar infarction group than those of the healthy control group. A positive correlation between modulus over vessel ROIs and age was observed. However, no significant correlation was found between sex and the regional biomechanical properties of the vessel ROIs.Conclusion: Results supported the hypothesis and suggest that biomechanical properties may be of utility in diagnosis of lacunar infarction.Keywords: magnetic resonance elastography, MRE, cerebral vasculature, lacunar infarction, biomechanical properties